Socialization causes long-lasting behavioral changes - Gil Martí, Beatriz (2024)
In modern human societies, social isolation acts as a negative factor for health and life quality.On the other hand, social interaction also has profound effects on animal and human, impactingaggressiveness, feeding and sleep, among many other behaviors. Here, we observe that in the flyDrosophila melanogaster these behavioral changes long-last even after social interaction has ceased, suggesting that the socialization experience triggers behavioral plasticity. These modified behaviors maintain similar levels for 24 h and persist up to 72 h, although showing a progressive decay. We also find that impairing long-term memory mechanisms either genetically or by anesthesia abolishes the expected behavioral changes in response to social interaction. Furthermore, we show that socialization increases CREB-dependent neuronal activity and synaptic plasticity in the mushroom body, the main insect memory center analogous to mammalian hippocampus. We propose that social interaction triggers socialization awareness, understood as long-lasting changes in behavior caused by experience with mechanistic similarities to long-term memory formation.